2015
DOI: 10.1371/journal.pone.0116765
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and Repellent Activity of Siparuna guianensis Aubl. (Negramina) against Aedes aegypti and Culex quinquefasciatus

Abstract: This study investigated the toxic effects of essential oils isolated from Siparuna guianensis against Aedes aegypti, Culex quinquefasciatus (eggs, larvae, pupae, and adult) and Aedes albopictus (C6/36) cells. The oviposition-deterring activity, egg viability, and repellence activity in the presence of different essential oils concentrations were determined. The essential oils showed high toxicity to all developmental stages of A. aegypti and C. quinquefasciatus. Furthermore, the oils also showed high repellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 28 publications
(34 reference statements)
3
46
1
Order By: Relevance
“…Phytochemical studies have shown that essential oils can be obtained from dried and fresh leaves, as well as from stems and fruits; however, the leaves comprise the part of the plant with the highest yield in extraction according to the literature on S. guianensis (Aguiar et al, 2015); therefore, the leaves were chosen as the object of this study. The extraction of the essential oil from the plant was performed by the hydrodistillation process using the Clevenger apparatus.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phytochemical studies have shown that essential oils can be obtained from dried and fresh leaves, as well as from stems and fruits; however, the leaves comprise the part of the plant with the highest yield in extraction according to the literature on S. guianensis (Aguiar et al, 2015); therefore, the leaves were chosen as the object of this study. The extraction of the essential oil from the plant was performed by the hydrodistillation process using the Clevenger apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…They were then crushed and submitted to hydrodistillation extraction in a Clevenger apparatus (Aguiar et al, 2015). A mixture of 300 g of fresh crushed leaves and 1000 mL of distilled water was heated in a 2-L flask, and the vapors generated were directed to a condensation column coupled to a cooling system.…”
Section: Obtaining the Essential Oilmentioning
confidence: 99%
See 3 more Smart Citations